2022
DOI: 10.1002/mds.29137
|View full text |Cite
|
Sign up to set email alerts
|

Nigral Neurons Degenerating in Parkinson's Disease Express the Angiotensin Receptor Type 1 Gene

Abstract: © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…22 Interestingly, here, we identified that a natural compound derived from plantain seeds, PMS, could alleviate SN damage in PD mice by reducing microglia polarization. 10 We therefore thought that PMS could serve as a promising drug for PD treatment.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Interestingly, here, we identified that a natural compound derived from plantain seeds, PMS, could alleviate SN damage in PD mice by reducing microglia polarization. 10 We therefore thought that PMS could serve as a promising drug for PD treatment.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Parkinson’s disease (PD) is known as a common neurodegenerative disease with major clinical manifestations of motor dysfunction, such as cognitive impairment. , PD usually occurs in people with the age of over 65 and is caused by the progressive degeneration of dopaminergic neurons in the substantia nigra (SN). The cause of PD is still elusive. Previous studies have demonstrated that the pathogenesis of PD is related to aging factors, environmental factors, genetic factors, oxidative stress, free radical formation, and associated nerve inflammation, but recent evidence suggests that chronic nerve inflammation caused by microglia activation may be important in the degenerative process. , Activated microglia are a major factor in neuroinflammation and dopaminergic neurodegeneration. , Overactivation of microglia results in the release of several neurotoxic factors, which contributes to the process of dopaminergic neurodegeneration. , Therefore, inhibition of microglial activation may contribute to the treatment and prevention of PD. In addition, finding more drugs is needed to combat this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly (Labandeira-Garcia and Parga, 2022), AT1 gene expression has been recently revealed as a major marker of dopaminergic neuron vulnerability in humans (Kamath et al, 2022). In rats, MetS also induced the increase in circulating levels of LIGHT and other major pro-inflammatory cytokines, together with an increase in 27-OHC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory and others have involved the brain renin-angiotensin system (RAS) in progression of Parkinson's disease and other neurodegenerative diseases by enhancing neuronal oxidative stress and neuroinflammatory processes (Campos and Pacheco, 2020;Labandeira-Garcia et al, 2013;Labandeira-Garcia et al, 2017;Wright and Harding, 2019). Interestingly (Labandeira-Garcia and Parga, 2022), a recent study has shown that the population of human dopaminergic neurons most vulnerable to degeneration in Parkinson's disease can be identified by their high expression of angiotensin type-1 (AT1) gen (Kamath et al, 2022). Dysregulation of the tissue RAS also plays a major role in several of the above-mentioned components of the MetS.…”
Section: Introductionmentioning
confidence: 99%
“…They act by antagonizing the angiotensin II (AT 1 ) receptor. It happens that this receptor, expressed in neurons, is a potential target of neurodegenerative diseases [83][84][85][86][87][88][89][90][91][92]. Animal models of neurodegenerative diseases have been instrumental in demonstrating that candesartan can cross the blood-brain barrier and act on receptors expressed in neural cells.…”
Section: Is It Good To Have Chronic Low Blood Pressure?mentioning
confidence: 99%